Gentiocrucines A–E, Five Unusual Lactonic Enamino Ketones from Swertia macrosperma and Swertia angustifolia - Wang, Hong-Ling; He, Kang; Geng, Chang-An; Zhang, Xue-Mei; Ma, Yun-Bao; Luo, Jie; Chen, Ji-Jun (Planta Medica, 2012)
Five unusual lactonic enamino ketones, gentiocrucines A–E (1–5), were isolated from Swertia macrosperma and S. angustifolia. Their structures were determined based on extensive spectroscopic analyses (IR, UV, MS, 1D- and 2D-NMR). By anti-HBV assay on the HepG 2.2.15 cell line in vitro, compound 1 inhibited both the secretion of hepatitis B virus surface antigen (HBsAg) and hepatitis B virus e antigen (HBeAg) with IC50 values of 3.14 and 3.35 mM, and compound 5 only inhibited the secretion of HBsAg with an IC50 value of 2.07 mM.
Keywords: gentiocrucines A–E; Swertia macrosperma; Swertia angustifolia; Gentianaceae; lactonic enamino ketones; anti-HBV activity